Estudio de la viabilidad para el desarrollo de una aplicación móvil de ventas online para microempresas de repuestos de motos en la ciudad de Babahoyo. - Valverde Acosta, Antonio Adolfo (2022)
E-commerce has been growing considerably since the start of the pandemic, causing many markets in Ecuador to be considerably affected, causing them to face new challenges in marketing their products. The objective of the case study is to determine the feasibility for the development of an online sales mobile application for motorcycle spare parts micro-enterprises in the city of Babahoyo, offering the facility for users to make their purchases from the comfort of their homes, as soon as possible. , the methodology used in the case study is the quantitative method; As an instrument for collecting information, surveys were chosen, in order to know the level of acceptance and usability, obtaining significant data to carry out the respective tabulation and analysis, with the technical and economic feasibility study it can be concluded that we would need an investment initial investment of $1,690.35 to start the project, generating a return per year of (-1,150.35) which tells us that the investment could not be recovered, generating significant losses, which means that the project would not be viable if it runs in that market.